Problematika Penggunaan Gadget dalam Pembelajaran Masa Pandemi Covid-19 (Dampak dan Solusi bagi Kesehatan Siswa) - Adib, Hamdan (STAI Auliaurrasyidin Tembilahan, 2021)
The purpose of this study was to determine the effect of learning innovation during the Covid-19 pandemic and its relation to students' physical and mental health. The method used was a qualitative method using library research. The study showed that during the Covid-19 Pandemic, the teachers and students conducted their teaching and learning using media such as laptops, smartphones, or tablets connected through the network by providers or WiFi. Students' physical health was distracted due to the duration of using those media was too long. At the same time, insufficient supervision by parents also affected their psychological health since all information spread very quickly without any qualified filter. However, teachers also experienced the same cases as students' have. This study suggests that parents should take action not only to monitor the duration of their children's learning but also the content they access.